2018
DOI: 10.1071/rdv30n1ab52
|View full text |Cite
|
Sign up to set email alerts
|

52 Difference of Seminal Plasma Proteins in Good- and Poor-Freezability Boar Ejaculates

Abstract: Seminal plasma is the semen components that maintain sperm metabolism, pH and osmolality. Fibronectin (FN1) and glutathione peroxidase (GPX5) are the seminal plasma proteins that play an important role on the boar sperm functions. The purpose of the present study was to determine the differences in GPX5 and FN1 contents in the boar semen having good, moderate, and poor freezability. A total of 38 ejaculates from 25 boars with proven fertility were included in the experiment. All the ejaculates included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…A positive correlation between the heparin-binding protein, osteopontin, and fertility has previously been described [24], while negative correlation to fertility for three other proteins has been observed. In addition, a higher quantity of the heparin-binding protein, fibronectin, has been reported in boar semen samples with high freezability than in those with poor freezability [25]. In agreement with previous results [4], phosphorylcholine-binding proteins were found to be abundant in the present study, although no difference between seasons was found.…”
Section: Discussionsupporting
confidence: 92%
“…A positive correlation between the heparin-binding protein, osteopontin, and fertility has previously been described [24], while negative correlation to fertility for three other proteins has been observed. In addition, a higher quantity of the heparin-binding protein, fibronectin, has been reported in boar semen samples with high freezability than in those with poor freezability [25]. In agreement with previous results [4], phosphorylcholine-binding proteins were found to be abundant in the present study, although no difference between seasons was found.…”
Section: Discussionsupporting
confidence: 92%
“…FN1 is considered a molecular marker for boar sperm freezability since it presents different concentrations of high and low freezability among males [12]. These differences were also confirmed by Rungruangsak et al [61]. FN1 is related to defects of the intermediate tract and tail of the spermatozoon.…”
Section: Fibronectinsmentioning
confidence: 65%
“…In boars, FN-1 is one of the most abundant proteins found in the seminal plasma [ 168 ], which has been found to be negatively associated with the proportion of sperm tail abnormalities [ 161 ]. Rungruangsak et al [ 169 ] have observed significant fluctuations of FN-1 in boar semen according to their freezability, with the highest levels of the protein found in good freezers, suggesting that the protein could become a potential freezability marker for boar semen cryopreservation. This finding was supported by Vilagran et al [ 170 ], according to whom FN-1 could stabilize boar sperm activity and provide defense to spermatozoa during the freeze–thaw process.…”
Section: Protein Markersmentioning
confidence: 99%